Faecal calprotectin is a surrogate marker of biliary inflammation in primary sclerosing cholangitis associated inflammatory bowel disease. Issue 6 (18th March 2022) - Pavlidis, Polychronis; Joshi, Deepak; El Sherif, Yasser; Warner, Ben; Gulati, Shraddha; Alexander, James; Cross, Gemma; Dew, Tracy; Arqoub, Hadil Abu; Devlin, John; Heneghan, Michael; Dubois, Patrick; et al.
Abstract : Objective: Faecal calprotectin (fCAL) is an established marker of intestinal inflammation in inflammatory bowel disease (IBD). Disproportionally high fCAL levels, for the severity of intestinal inflammation, have been previously observed in primary sclerosing cholangitis associated IBD (PSC-IBD). The aim of this study was to test the hypothesis that fCAL is a marker of biliary injury in PSC-IBD. Methods: We used two cohorts: (1) post hoc analysis of a colonoscopic surveillance study allowing correlation of fCAL to endoscopic severity as measured by the ulcerative colitis endoscopic index of severity (UCEIS) in PSC-IBD (n=20) and ulcerative colitis (UC, n=20) and (2) prospective recruitment of patients attending for endoscopic retrograde cholangiopancreatography allowed the correlation of fCAL to biliary calprotectin (n=8). Results: A strong correlation was seen between fCAL and UCEIS in UC (r=0.821, 95% CI (0.585 to 0.929), p<0.0001). In PSC-IBD, the correlation was weaker (r=0.596, 95% CI (0.195 to 0.8260), p=0.006). PSC-IBD patients with endoscopically quiescent colitis (UCEIS: 0–1) had higher fCAL than patients with UC (279 µg/g, IQR (68–601) vs 30 µg/g, IQR (14–107), p=0.015) . This was associated with higher risk of biliary complications like need for antibiotics or instrumentation (HR 16.39, 95% CI (2.98 to 90.25)) rather than colitis flares (follow-up: 12 months). Calprotectin measured in faeces correlated positively with biliary calprotectin (r=0.898, p=0.0024). Conclusion: fCAL is a surrogate marker for biliary inflammation in PSC-IBD. Trial registration number: NCT02543021 .